Analisis Pengaruh Supply Chain Management terhadap Loyalitas Konsumen - Tommy Setiawan Ruslim (JIEMS (Journal of Industrial Engineering and Management Systems), 2017)
In this day and age, competition in the competitive business world, every company should be able to see far ahead a wide range of factors that arise to deal with changing conditions. They must analyze whether the factors facing it is an opportunity and a chance or otherwise a threat to the company. Supply chain management in order to overcome supply problems in the state of the product available and feasible consumption. Supply control is important to control the supply of the deficiency and excess production, supply, or demand. Shortage of these products will lead to complaints from consumers and companies will lose a number of opportunities to generate income. Meanwhile, the brand image of the item will be bad. As a result, consumers are becoming less loyal to consume goods, and even more negative impact consumer inadvertently talks by word of mouth (mouth to mouth) to other consumers not to purchase it at retail. While the excess inventory will result in losses for producers. The purpose of this study was to determine whether there is a significant influence of supply chain management to customer loyalty on Supermarket "DB" at Duta Mas. By taking a sample of 60 respondents, but only 57 are completed and after processing, the results obtained have a significant influence of supply chain management to customer loyalty on Supermarket "DB" at Duta Mas.Keywords: Supply Chain Management, Loyalitas, Regresi Linier Sederhana